Pentazocine Protects SN4741 Cells Against MPP+-Induced Cell Damage via Up-Regulation of the Canonical Wnt/β-Catenin Signaling Pathway - Wang, Jiancai; Gu, Jintao; Wu, Hao; Zhu, Gang; Feng, Dayun; Li, Yuqian; Guo, Wei; Tian, Keyong; Gao, Guodong; Gao, Li (Frontiers in Aging Neuroscience, 2017)
The Wnt/β-catenin signaling pathway has been linked to many neurodegenerative diseases including Parkinson’s disease (PD). A glycoprotein named Dickkopf-1(Dkk1) can combine with the receptor complex on cell membrane to inhibit Wnt/β-catenin signaling. Opioids, a series of compounds including morphine, fentanyl and pentazocine, have been reported to contribute to the up-regulation of Wnt/β-catenin signaling. Naloxone is an antagonist that has been used as an antidote to opioids through mu-opioid receptor. MPP+, which serves as a selective toxin for dopaminergic neurons, has been used to create experimental models of PD. In our study, we examined the protective effects of pentazocine against MPP+-induced cell death in the nigral dopaminergic cell line, SN4741 and tried to elucidate the molecular mechanisms underlying such protective effects. The data showed that pretreatment with pentazocine significantly rescued the SN4741 cell against MPP+. Moreover, the MPP+-exposed SN4741 cells exhibited a down-regulation of β-catenin, which could be restored by treatment with pentazocine. However, Dkk1 but not naloxonewas associated with the abrogation of protective effect of pentazocine. These results suggest that pentazocine alleviates MPP+-induced SN4741 cells apoptosis via the up-regulation of canonical Wnt/β-catenin signaling.